2021
DOI: 10.1038/s41416-021-01620-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of KRAS, BRAF and microsatellite instability status after cytoreductive surgery and HIPEC in a national cohort of colorectal peritoneal metastasis patients

Abstract: Background Patients with metastatic colorectal cancer (mCRC) carrying BRAF (mutBRAF) or KRAS mutation (mutKRAS) have an inferior prognosis after liver or lung surgery, whereas the prognostic role in the context of peritoneal metastasis (PM) after cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) has been less investigated. Methods In total, 257 patients with non-appendiceal PM-CRC were included from the Norwegian National Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
2
23
1
Order By: Relevance
“…In terms of survival, median overall survival was 33 months (95% CI 28–38 months) for colorectal cancer and 130 months (95% CI 98–162 months) for pseudomyxoma patients [ 122 , 123 ]. Current nationwide Norwegian data report a median survival of 49 months from the time of CRS HIPEC and a 5-year overall survival of 40.1% for colorectal cancer [ 103 ], in concordance with results from British and French tertiary referral centers [ 22 , 95 ]. These outcomes are realistic figures that have been met and exceeded by specialized Swiss centers [ 104 , 105 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In terms of survival, median overall survival was 33 months (95% CI 28–38 months) for colorectal cancer and 130 months (95% CI 98–162 months) for pseudomyxoma patients [ 122 , 123 ]. Current nationwide Norwegian data report a median survival of 49 months from the time of CRS HIPEC and a 5-year overall survival of 40.1% for colorectal cancer [ 103 ], in concordance with results from British and French tertiary referral centers [ 22 , 95 ]. These outcomes are realistic figures that have been met and exceeded by specialized Swiss centers [ 104 , 105 ].…”
Section: Discussionsupporting
confidence: 73%
“…However, a national prospective cohort of Norvegian patients treated with CRS HIPEC between 2005 and 2015 did not see any differences in survival according to KRAS of BRAF mutations. Interestingly, patients who presented with a BRAF mutation and microsatellite instability had significantly better survival [ 103 ]. In a further analysis of 505 patients who underwent CRS HIPEC at 4 European centres, KRAS mutations and to a lesser extent positive nodal stage were independent predictors of peritoneal recurrence following CRS HIPEC [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have identified RASmt as a negative prognostic marker after cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal metastasectomy [38], but a recent Norwegian study found a similar OS of around 49 months after cytoreductive surgery with HIPEC irrespective of RAS and BRAF status [39]. In the latter study a BRAFmt subgroup with dMMR had superior survival among the patients with BRAFmt and this has also been reported in an unselected CRC cohort [40].…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that patients with CRC and peritoneal metastases may have worse prognoses with RAS mutations, though these data are mixed, and we did not observe any notable trend for KRAS mutations in this study. [17][18][19] mutations have also been associated with poor OS in earlier-stage colon cancers, although their impact on metastatic disease has not been fully characterized. 20 Patients with metastatic CRC have more consistently demonstrated poor survival with BRAF mutations, although the incidence of these mutations is low at 0%-9%.…”
Section: Discussionmentioning
confidence: 99%